Biomimetic corneal stroma using electro-compacted collagen. (1st September 2020) - Chen, Zhi; Liu, Xiao; You, Jingjing; Song, Yihui; Tomaskovic-Crook, Eva; Sutton, Gerard; Crook, Jeremy M.; Wallace, Gordon G.
Abstract: Engineering substantia propria (or stroma of cornea) that mimics the function and anatomy of natural tissue is vital for in vitro modelling and in vivo regeneration. There are, however, few examples of bioengineered biomimetic corneal stroma. Here we describe the construction of an orthogonally oriented 3D corneal stroma model (3D-CSM) using pure electro-compacted collagen (EC). EC films comprise aligned collagen fibrils and support primary human corneal stromal cells (hCSCs). Cell-laden constructs are analogous to the anatomical structure of native human cornea. The hCSCs are guided by the topographical cues provided by the aligned collagen fibrils of the EC films. Importantly, the 3D-CSM are biodegradable, highly transparent, glucose-permeable and comprise quiescent hCSCs. Gene expression analysis indicated the presence of aligned collagen fibrils is strongly coupled to downregulation of active fibroblast/myofibroblast markers α-SMA and Thy-1, with a concomitant upregulation of the dormant keratocyte marker ALDH3. The 3D-CSM represents the first example of an optimally robust biomimetic engineered corneal stroma that is constructed from pure electro-compacted collagen for cell and tissue support. The 3D-CSM is a significant advance for synthetic corneal stroma engineering, with the potential to be used for full-thickness and functional cornea replacement, as well as informing in vivo tissue regeneration. Statement of Significance: This manuscript represents the first example of a robust, transparent, glucose permeable and pure collagen-based biomimetic 3D corneal stromal model (3D-CSM) constructed from pure electro-compacted collagen. The collagen fibrils of 3D-CSM are aligned and orthogonally arranged, mimicking native human corneal stroma. The alignment of collagen fibrils correlates with the direction of current applied for electro-compaction and influences human corneal stromal cell (hCSC) orientation. Moreover, 3D-CSM constructs support a corneal keratocyte phenotype; an essential requirement for modelling healthy corneal stroma. As-prepared 3D-CSM hold great promise as corneal stromal substitutes for research and translation, with the potential to be used for full-thickness cornea replacement. Graphical abstract: Image, graphical abstract